PENTINGNYA PENDIDIKAN KEWARGANEGARAAN UNTUK MENANAMKAN JIWA KEBANGSAAN PADA GENERASI MUDA MILENIAL - Arofah, Zahwa Linata; Ilham, Maulid Dina Rahmawati; Walia, Nur (Cahaya Ilmu Bangsa, 2025)
Citizenship education plays an essential role in shaping the national spirit of our youth. This study delves into the importance of citizenship education in cultivating a sense of national identity, utilizing a literature-based approach that draws from a variety of relevant sources. There are several compelling reasons why citizenship education is vital. First, it enhances students' understanding of national values, history, and identity, providing a solid foundation for a vibrant national spirit. Additionally, it promotes active participation through engaging activities, fostering a sense of responsibility, social skills, and leadership qualities that empower young individuals to make positive contributions to society. Moreover, citizenship education nurtures tolerance, respect for diversity, and a comprehensive understanding of human rights—elements that are crucial for building an inclusive national outlook. The millennial generation is key to the nation’s development. Through effective citizenship education, they can cultivate a deeper appreciation for the significance of active engagement, social empathy, and commitment to their communities and country. This study emphasizes the necessity of enhancing the curriculum, providing adequate teacher training, and implementing innovative teaching methods to strengthen the national spirit among the youth. By refining these essential components, citizenship education can play a vital role in shaping responsible citizens committed to the nation’s advancement. Pendidikan Kewarganegaraan memegang peranan yang sangat penting dalam membangun semangat kebangsaan di kalangan generasi muda. Penelitian ini bertujuan untuk menggali lebih dalam mengenai signifikansi Pendidikan Kewarganegaraan dalam menanamkan rasa kebangsaan, melalui pendekatan studi literatur. Berbagai sumber yang relevan mengenai Pendidikan Kewarganegaraan dan pengembangan jiwa kebangsaan akan dianalisis secara mendetail. Dalam penelitian ini, sejumlah alasan diidentifikasi sebagai bukti betapa mendesaknya Pendidikan Kewarganegaraan bagi pengembangan jiwa kebangsaan generasi muda. Pertama, pendidikan ini memberikan pemahaman mendalam tentang nilai-nilai kebangsaan, sejarah, dan identitas nasional—semua itu merupakan fondasi bagi terbentuknya jiwa kebangsaan yang kokoh. Kedua, melalui kegiatan yang bersifat partisipatif, Pendidikan Kewarganegaraan membentuk rasa tanggung jawab, keterampilan sosial, dan jiwa kepemimpinan, yang mendorong generasi muda untuk berperan aktif serta memberikan kontribusi positif kepada masyarakat. Lebih jauh, Pendidikan Kewarganegaraan juga berperan dalam mengembangkan sikap toleransi, menghargai keberagaman, dan memahami hak asasi manusia—semua aspek yang krusial dalam menciptakan jiwa kebangsaan yang inklusif. Generasi milenial, sebagai agen perubahan, memiliki posisi kunci dalam proses pembangunan bangsa. Dengan Pendidikan Kewarganegaraan yang efektif, mereka dapat meningkatkan kesadaran akan pentingnya partisipasi aktif, empati sosial, dan pengabdian kepada masyarakat serta negara. Penelitian ini menekankan pentingnya penguatan kurikulum, pelatihan guru yang memadai, dan penerapan metode pembelajaran yang inovatif untuk mencapai tujuan pembentukan jiwa kebangsaan yang lebih baik di kalangan generasi muda.